Effectiveness of Agricultural Extension Communication of Spinach Farming - Pasaribu, Asriel Sumurung; Novanda, Ridha Rizki (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2022)
This study aimed to analyze Agricultural Extension Communications' effectiveness in Spinach Farming in Kasturi Farmer Groups in Pulo Jantan Village, Na IX-X District. This study was conducted on a Kasturi farmer group in Pulo Jantan Village, NA IX-X District, Labuhanbatu Utara Regency. The research location was determined intentionally (purposively), considering that the farmer group was classified as active in extension activities. The method used to collect data is using interview techniques using prepared questionnaires. Data analysis was performed using descriptive analysis to get a clearer picture and detail about a situation based on the information obtained, collected, classified, and interpreted to get the information necessary to analyze the existing problems. The result is that communication of agricultural extension workers in spinach farming in the Kasturi farmer group in Pulo Jantan Village, Na IX-X District, is categorized as effective. This is seen from the percentage of 3 aspects, namely cognitive, affective and conative, in the effective category. The most practical aspect of counseling communication is the cognitive aspect, with the highest percentage of effective categories. It is better if agricultural extension workers can adapt the material presented according to the problems farmers face.